Profile of Pancasila Students: Implementation of Diversity in MBKM Student's Stories in UST Yogyakarta - Onok Yayang Pamungkas; Anang Sudigdo (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
This study is an attempt to investigate the values ​​of the Pancasila Guru Profile in the fairy tales of MBKM students at Universitas Sarjanawiyata Tamansiswa Yogyakarya. The object of the research is fairy tale data from 150 MBKM students from 3 universities. The research data is in the form of information about: 1) Name of students; 2) Origin of Higher Education; 3) City of origin; 4) The title of the fairy tale; 5) The theme of fairy tales is related to the values ​​of the Pancasila Student Profile; 6) Basic inspiration for taking fairy tale topics; and, 7) The purpose of planting fairy tale characters. The results showed that people from the DIY and Central Java provinces still dominated as students with the highest number of students in the MBKM program. The domination of these 2 provinces will affect the cultural aspects and values ​​of the Pancasila Student Profile from other provinces. The tales that are made imply the plurality of Indonesian society. In turn, MBKM students' fairy tales are a real vehicle that can guide students about diversity that is relevant to the values ​​of the Pancasila Student Profile.